Novel method for assessment of durability of sailing protective garments in simulated environments - Watson, C. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Competitive sailing is one of the extreme sports which is performed at high speeds in challenging weather and environmental conditions with strenuous physical demands placed on the athlete. Sailing garments need to satisfy numerous performance requirements, such as being ergonomically and thermo physiologically comfortable, highly aerodynamic, light weight, protect from UV radiation and the elements, and most importantly be strong to withstand constant abrasion and flexing but also with durability to withstand these rigours over the life of the garment. The fabrics and materials comprising these garments must remain waterproof after dynamic three-dimensional abrasion, multi-directional impact and extended wear and tear both in dry and especially wet conditions. Any leaks in these garments are generally considered a fail by most sailors and the garment would then to be replaced. Standard bench top tests exist for testing the materials for such attributes as abrasion resistance, puncture and tear resistance, generally separately for each attribute. In addition standardised hydrostatic head testing is common; however it does not give any indication as to how the fabric or material will perform in protecting the athlete after extended periods of use, especially in wet conditions. Waterproofing and breathability are two selected critical attributes that were addressed in the present study. Suitable novel experimental methodology, instrumentation and methods were developed to assess durability of these attributes for a number of materials containing breathable membranes, after prolonged simulated use in wet conditions. Results clearly indicate that the performance of the materials intended for sailing apparel must be considered not only as separate attributes in dry conditions but also in combination in dynamic wet conditions